EXPERIMENTAL EVALUATION OF AMPLITUDE MODULATION AND FREQUENCY MODULATION ON CYLINDRICAL ROLLER BEARING SUBJECTED TO STATIC LOAD - MAGIANO FAIZUL AGUS (NIM : 131 05 038); Pembimbing : Prof. Dr. Ir. Komang Bagiasna, KEMAL
Any bearing defects has a certain vibration response characteristics. By knowing the theoretical bearing defect frequencies, any defects occur in the bearings can be analyzed. In general, frequency of defects has sidebands, which indicates that the signal is modulated. This research was made to study the vibration response characteristics in the roll bearings due to static load and wavy bearing surface (waviness). The experimental part of this research consist of FRF (Frequency Response Function) measurement to obtain the dynamic characteristics of the test object and power spectrum testing to measure the vibration response that occurs in the bearing at various speeds and load. Shaft speed and static load are being varied stepwise from 300 RPM to 1200 RPM with step interval of 300 RPM while the static load are varying by 200N, 400N, and 600N in the direction of horizontal, vertical and combination of both. Experimental result reveals Roll Passage Frequency (RPF) and its sidebands due to static load. In addition, from the tested bearing were found waviness at inner-race with waviness order of 4 and waviness at outer-race with waviness order of 6.